2006
DOI: 10.3177/jnsv.52.54
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Plasma Metabolite Concentration after Ingestion of Lemon Flavonoids and Their Aglycones in Humans

Abstract: SummaryThe concentrations of metabolites in human plasma after ingestion of flavanone glycosides (FG) and their aglycones (FA) in lemon were examined. FG consisting abundantly of eriocitrin were prepared from lemon peel and FA consisting abundantly of eriodictyol were prepared from FG by treatment with ␤-glucosidase. Eriodictyol, homoeriodictyol, and hesperetin in plasma up to 4 h after ingestion of FG with water or FA with water by subjects were not detected in plasma of non-enzyme treatment but in plasma aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 27 publications
4
44
0
1
Order By: Relevance
“…1 (Kawai et al, 1999;Miyake et al, 2007). LF, which is prepared from lemon peel and predominantly contains eriocitrin, has been reported to have low bioavailability when orally ingested by humans (Miyake et al, 2006b), although it exhibited bioactivities such as a suppressive effect on oxidative stress in experimental animals (Miyake et al, 1998(Miyake et al, , 2006a). An oral intake test in rats has shown that eriocitrin is absorbed after it is converted to eriodictyol of an aglycone by intestinal bacteria (Miyake et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 (Kawai et al, 1999;Miyake et al, 2007). LF, which is prepared from lemon peel and predominantly contains eriocitrin, has been reported to have low bioavailability when orally ingested by humans (Miyake et al, 2006b), although it exhibited bioactivities such as a suppressive effect on oxidative stress in experimental animals (Miyake et al, 1998(Miyake et al, , 2006a). An oral intake test in rats has shown that eriocitrin is absorbed after it is converted to eriodictyol of an aglycone by intestinal bacteria (Miyake et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Change of flavonoids in LF by enzyme treatment LF was prepared from lemon peel using the reported method (Miyake et al, 2006b). The solution (5 mL) prepared with 10 mg/mL of LF, 1 mg/mL of each enzyme (cellulase, hesperidinase, naringinase, pectinase) and 50 mM of sodium acetate-HCl buffer solution (pH 3.5) at final concentration was incubated at 37℃ for 3 h. The reaction was carried out at pH 3.5, because enzymes have been used in citrus juice of pH 3-4 in citrus factories.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations